2015
DOI: 10.1108/ijem-05-2013-0081
|View full text |Cite
|
Sign up to set email alerts
|

School teachers’ job satisfaction and personal characteristics

Abstract: Purpose – The purpose of this paper (based on the relevant literature) is to: investigate, through empirical analysis, primary school teachers’ perceptions regarding their job satisfaction, and examine whether or not the personal characteristics of primary school educators (such as gender, age, family status, educational level, and the total years of service in public primary education) have any impact on their job satisfaction. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 63 publications
5
47
1
3
Order By: Relevance
“…In a survey conducted by Saiti and Papadopoulos (2015), it was found out that a stable job, their relationship with the school's management and their colleagues, and the nature of the job itself, affect the level of satisfaction experienced by primary education teachers. In the same survey, it was shown that the remuneration offered to cover material needs does not affect the job satisfaction experienced by teachers, although their salaries have been significantly reduced due to the deep recession that the country is currently going through.…”
Section: Teachers' Job Satisfactionmentioning
confidence: 99%
“…In a survey conducted by Saiti and Papadopoulos (2015), it was found out that a stable job, their relationship with the school's management and their colleagues, and the nature of the job itself, affect the level of satisfaction experienced by primary education teachers. In the same survey, it was shown that the remuneration offered to cover material needs does not affect the job satisfaction experienced by teachers, although their salaries have been significantly reduced due to the deep recession that the country is currently going through.…”
Section: Teachers' Job Satisfactionmentioning
confidence: 99%
“…Some studies find no significant link between teacher satisfaction and the variables of gender, age, or years of experience (Briones et al, 2010;Saiti & Papadopoulos, 2015). By contrast, in other studies, younger teachers report higher satisfaction than older teachers, and female teachers are more satisfied than male teachers (Ma & McMillan, 1999).…”
Section: Teacher Satisfaction and Associated Variablesmentioning
confidence: 88%
“…Similarly, Sarpkaya (2000) detected that teachers showed the least job satisfaction in income sub dimension. Income level and the money they receive affect teachers' job satisfaction (Saiti & Papadopoulos, 2015;Spector, 1997). AS the income increases, so does the job satisfaction (Abd-El-Fattah, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%